PERAN GENERASI BINA BANGSA (GENBI) DALAM MEMBERDAYAKAN MASYARAKAT PERBATASAN JAGOI BABANG KAB BENGKAYANG - Syarifah Ema Rahmaniah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This article discusses the role of GENBI in increasing the community participation in developing the Bidai craft in Jagoi Babang Bengka using incubator business program in cooperation with Bank Indonesia. This paper uses qualitative methods by using in depth interview towards Bidai craftsmen in Jagoi Babang and the community leaders who are competent about the issue of border development. Using Arstein Ladder method, it is identified that there is a significant increase of community participation in the business incubator program. It is on the fifth and the sixth phase, namely partnership and placation. The Synergy cooperation among government, the private sector and the community is needed in order to increase public participation. Government affirmative action becomes important to be pursued to control the bidai craft productivity and create a socio economic network among the craftsmen.